A Statistical Study of the Forestry in Ukraine - Kobylynska, Т. V.; Huseva, N. Yu. (Statistics of Ukraine, 2020)
The article is devoted to the analysis of the forestry in Ukraine as the reference point for further development of the framework for constructing the national forest account allowing for a description of interactions between economic activities and forests as a nature environment, and for consistent and comprehensive integration of environmental and economic problems in this field. The study covers the existing statistical definitions, classifications and the available statistical information about the forest, selected forestry indicators for Ukraine, the existing sources of data for the analysis of forestry, with proposing the necessary steps for further applications of forest accounting tools, in order to construct the forest account. It is pointed out that the forestry is represented by two large groups of institutional units: physical persons or groups of physical persons in form of households; legal entities, established and operated in keeping with the law, irrespective of what persons or entities may be their owners or managers. The main categories of legal entities are corporations, non-commercial organizations, and public administration bodies. It is determined that the main sources of data about the forest fund and forest resources of Ukraine are as follows: (i) statistical information based on the data from enterprises, obtained from official statistical observations of the State Statistics Service of Ukraine; (ii) administrative data based on the data from enterprises, obtained by public administration bodies (The State Service of Ukraine on Geodesy, Cartography and Cadastre, the State Agency of Forest Resources of Ukraine, the State Custom Service, the State Taxation Service) as part of functional responsibilities; (iii) the data of the national inventory of forests, obtained by the authorized bodies. The latest official data of the national forest inventory for Ukraine are available as of January 01, 2011, but these data have not been published yet in a proper manner. It is demonstrated that the official statistics cover a limited set of statistical data about the forestry due to the institutional constraints. A dynamic and structural analysis of the forest lands is explored, with outlining the main problems related with improving methodological approaches to the formation of the forestry statistics. The analysis allowed for determining the main areas of improvements in the forestry accounting and coming up with propositions of necessary steps to solve the problems of statistical studies of this industry.